Outcomes in adults with systolic blood pressure between 130 and 139 mmHg in Action to Control Cardiovascular Risk in Diabetes Blood Pressure trial and Systolic Blood Pressure Intervention Trial. Issue 8 (August 2020) - Contreras, Gabriel; Lu, Lingyi; Tamariz, Leonardo; Rocco, Michael V.; Papademetriou, Vasilios; Kostis, John B.; Pisoni, Roberto; Glasser, Stephen P.; Sweeney, Mary E.; Basile, Jan; Gren, Lisa H.; Zamanian, Sara; et al.
Abstract : Background: Patients with stage 1 systolic hypertension have increased risk of cardiovascular disease (CVD) events. Methods: Using Cox models, we assess the effect of targeting an intensive SBP goal of less than 120 mmHg compared with standard SBP goal of less than 140 mmHg on the risk of CVD events in adults with stage 1 systolic hypertension with diabetes mellitus enrolled in Action to Control Cardiovascular Risk in Diabetes Blood Pressure trial (ACCORD BP) ( n  = 1901) and without diabetes mellitus enrolled in Systolic Blood Pressure Intervention Trial (SPRINT) ( n  = 3484) that used identical SBP goal interventions. Outcomes: In ACCORD BP, the primary composite CVD outcome was the first occurrence of myocardial infarction, stroke, or CVD mortality. In SPRINT, the primary composite CVD outcome was the first occurrence of myocardial infarction, other acute coronary syndrome, stroke, heart failure, or CVD mortality. Results: In SPRINT, targeting an intensive SBP goal significantly reduced the risk of the primary CVD outcome [hazard ratio 0.75 (95% confidence interval, 0.58–0.98); events 1.78 vs. 2.37%/year]. In ACCORD BP, the relationships of SBP goal with the primary CVD outcome was modified by the glycemia goal intervention (interaction P  = 0.039). In the standard glycemia subgroup (A1c target 7–7.9%), intensive SBP goal significantly reduced the risk of the primary CVD outcome [hazard ratio 0.61 (0.40–0.94); events 1.63 vs. 2.56%/year]. In the intensive glycemia subgroup (A1c target <6%), the risk of the primary CVD outcome was not significantly different between groups [hazard ratio 1.20 (0.76–1.89); events 1.91 vs. 1.60%/year]. Conclusion: Targeting an intensive SBP goal significantly reduced the risk of CVD events in patients with stage 1 systolic hypertension without diabetes and with diabetes on standard glycemia goal. Abstract : Supplemental Digital Content is available in the text